EDUKASI PENGENALAN INTERNET POSITIF DAN NEGATIF UNTUK MENINGKATKAN KESADARAN DIGITAL MELALUI PENDEKATAN EDUKATIFDI SD NEGERI 08 KEPAHIANG - Pradana, Rirafli Arya; Fetriani (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The rise of negative content such as pornography, gambling, and violence on the internet is making us increasingly concerned about the fate of the younger generation, especially in Indonesia, which has been consistently rated as the largest user of pornographic websites. This is further exacerbated by the ease of internet access available today. The purpose of this activity is to provide training to students on how to use the internet effectively. One method that can be used is a presentation to students. explaining the concept of positive internet usage, its positive and negative impacts, and directly influencing students to understand the internet’s impacts. The training results show that many students have gained a better understanding of the impact of the internet. This success can be seen in the satisfaction of participants after participating in this activity. This is because students who did not understand what the internet is and its impacts are, now they able to understand about the internet.